Ultrasonic Assisted Cloud Point Extraction-Scanometry, A New Method for the Simultaneous Preconcentration and Determination of Two Dyes; Application for the Determination of Crystal Violet and Auramine O - Shokrollahi, A.; Behrooj Pili, H. (Current Analytical Chemistry, 2017)
Background: The solution scannometric technique was introduced recently by Abbaspour et al. They used commercially available flatbed-scanners for obtaining the images of color solutions. The obtained images have been transferred to computer for analyzing and determining the intensity of color solutions. The method is based scanning of solution phase, in Plexiglas® cells. Finally the RGB (red, green and blue) color model was used in color monitor. In our previous work CPE-Scanometry was introduced for determination of one component (fast green FCF) in aqueous solutions. Methods: In this work for the first time UACPE-Scanometry as new, fast, facile, cheap and sensitive method was used for simultaneous separation, preconcentration and determination of Auramine O (AO) and Crystal Violet (CV) in aqueous samples. For the cloud point extraction, aliquots of solution containing the analytes, Triton X-114 (0.23% w/v), KCl (0.05 mol L-1) and NaClO4 (0.05 mol L-1) electrolytes were mixed in 15 mL centrifuge tube then pH of solution adjusted to the desired value. The solution was diluted to the mark with double distilled water and allowed to stand for 2.5 min in ultrasonic bath for accelerating phase separation. separation of the aqueous and surfactant-rich phase was accomplished by centrifugation for 10 min at 3500 rpm. Then the dilute phase was carefully removed with a pipette and the surfactant rich phase was diluted with ethanol to 500 μL, and 480 μL of this solution was injected into the one cell on Plexiglas® sheet, and similar way to other cells. After shaking, the color cells were scanned with the scanner and the obtained images of the color solutions were analyzed to evaluate R, G and B contents by the developed software. Results: The influence of operation parameters including such as pH, concentrations of surfactant and electrolyte on the cloud point extraction of both dyes were investigated and optimum conditions were established. Under the optimum experimental conditions calibration graphs were linear in the range of 0.02-2.7 and 0.06-5.0 mg L-1 with detection limits of 0.01 and 0.04 mgL-1 for CV and AO, respectively. Also the precision (%RSD) for seven replicate determinations of the analytes was better than 2.45%. Finally, the proposed method was utilized successfully for the determination of CV and AO in surface water (river), tap water and industrial waste water samples. Conclusion: In this paper, CPE-Scanometry as a new method was used for the simultaneous determination trace amount of two dyes for the first time. Crystal violet and Auramine O were chosen as templates for this purpose. The proposed method employs cloud point extraction and the scanometry method. This method offers novelty, facility, high speed, sensitivity, low cost and safety.
Keywords: crystal violet